Tanggung Jawab Rumah Sakit Terhadap Kerahasiaan Rekam Medis (Medic Record) di Masa Pandemi Covid-19 - Made Bayu Bagaskara; A. A. Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Medical history is a file that contains important records or documents that contain the patient's identity in the examination, treatment, actions and services that have been provided to the patient. Medical records have a great influence on the legal relationship between hospitals and patients. This study examines two things, namely the legal arrangements related to the management of hospital patient files and the responsibility of the hospital to disclose the secret of medical records. The purpose of this study was to analyze the hospital's responsibility in the event of data leakage from the patient's medical history. This type of research is normative legal research, with an emphasis on legislation and literature studies, analyzing and revising applicable legal norms as the basis for problem solving. The results of the study indicate that the legal provisions contained in Article 58 of Law no. 36 of 2009 concerning health, hospitals can be sued for negligence in health services, including leaking medical secrets. And regulated in Article 58 of Law no. 36 of 2009 concerning Health, the hospital can be sued for compensation caused by errors or omissions in health services, including for leaking medical secrets.